Priorities for Patient‐Centered Outcomes Research: The Views of Minority and Underserved Communities. (20th May 2016) - Goold, Susan Dorr; Myers, C. Daniel; Szymecko, Lisa; Cunningham Collins, Carla; Martinez, Sal; Ledón, Charo; Campbell, Terrance R.; Danis, Marion; Cargill, Stephanie Solomon; Kim, Hyungjin Myra; Rowe, Zachary
Abstract : Objective: To learn how minority and underserved communities would set priorities for patient‐centered outcomes research (PCOR). Data Sources: Sixteen groups ( n = 183) from minority and underserved communities in two states deliberated about PCOR priorities using the simulation exercise CHoosing All Together (CHAT). Most participants were minority, one‐third reported income <10, 000, and one‐fourth reported fair/poor health. Design: Academic–community partnerships adapted CHAT for PCOR priority setting using existing research agendas and interviews with community leaders, clinicians, and key informants. Data Collection: Tablet‐based CHAT collected demographic information, individual priorities before and after group deliberation, and groups' priorities. Principal Findings: Individuals and groups prioritized research on Quality of Life, Patient‐Doctor, Access, Special Needs, and (by total resources spent) Compare Approaches. Those with less than a high school education were less likely to prioritize New Approaches, Patient‐Doctor, Quality of Life, and Families/Caregivers. Blacks were less likely to prioritize research on Causes of Disease, New Approaches, and Compare Approaches than whites. Compare Approaches, Special Needs, Access, and Families/Caregivers were significantly more likely to be selected by individuals after compared to before deliberation. Conclusions: Members of underserved communities, in informed deliberations, prioritized research on Quality of Life, Patient‐Doctor, Special Needs, Access, and Compare Approaches.